2004
DOI: 10.1029/2004jd004505
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long‐range‐transported pollution on the annual and diurnal cycles of carbon monoxide and ozone at Cheeka Peak Observatory

Abstract: [1] We assess the importance of distant pollution sources on the marine background by combining measurements of carbon monoxide (CO) and ozone (O 3 ) with model simulations from the GEOS-CHEM chemical transport model and two types of back trajectories. Measurements were made over a complete annual cycle from March 2001 to May 2002 at Cheeka Peak Observatory (CPO) in Washington State. Data from an earlier campaign (March-April 1997 and1998) were also incorporated. The seasonal cycles of CO and O 3 show a spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…During this sampling campaign, CPO was influenced by Asian pollution during our 15–16 March, 27–28 March, and 22–23 April 2002 sampling periods. This was determined from CPO observations of CO and aerosols [ Weiss‐Penzias et al , 2004], from the GEOS‐CHEM global model [ Liang et al , 2004], and suggested by our PCA results and trajectory classification. The 48‐hour sample of 15 March 2002 overlapped with the first transpacific event.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During this sampling campaign, CPO was influenced by Asian pollution during our 15–16 March, 27–28 March, and 22–23 April 2002 sampling periods. This was determined from CPO observations of CO and aerosols [ Weiss‐Penzias et al , 2004], from the GEOS‐CHEM global model [ Liang et al , 2004], and suggested by our PCA results and trajectory classification. The 48‐hour sample of 15 March 2002 overlapped with the first transpacific event.…”
Section: Resultsmentioning
confidence: 99%
“…This sampling period was also the only time triallate, endosulfan II, and endosulfan sulfate were detected. The presence of elevated concentrations of PAHs and pesticides (including the detection of pesticides not measured in other samples), changes in the normalized concentrations of PAHs and pesticides shown by PCA in section 3.5, back trajectories that pass over Asia, and the GEOS‐CHEM model predictions, suggest Europe and Asia as potential sources of these SOCs on 15–16 March, 27–28 March, and 22–23 April 2002 [ Weiss‐Penzias et al , 2004; Liang et al , 2004]. The estimated atmospheric half‐lives for the measured pesticides in the gas‐phase range from 2.2 days (cis‐nonachlor and trans‐nonachlor) to 1731 days (chlorothalonil) (EPI Suite v. 3.1.1, Environmental Protection Agency, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of satellite instruments have been measuring tropospheric CO globally over the past decade including MOPITT (2000-) (Edwards Published by Copernicus Publications on behalf of the European Geosciences Union. et al, 2006b;Emmons et al, 2007), SCIAMACHY (2002 (Bovensmann et al, 1999;Buchwitz et al, 2007;Burrows et al, 1995;de Laat et al, 2007), AIRS (2002-) (McMillan et al, 2005Warner et al, 2007;Yurganov et al, 2008), ACE-FTS (2003-) (Clerbaux et al, 2005, TES (2004-) (Lopez et al, 2008;Luo et al, 2007a;Rinsland et al, 2006), andIASI (2007-) (FortemsCheiney et al, 2009;Turquety et al, 2009). These satellite data expand the perspective offered by in situ observations, such as from the NOAA/GMD surface monitoring network (Novelli et al, 2003) and from commercial aircraft (Nedelec et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the CO lifetime in the troposphere (30Á90 d), the pollutant can be transported in continental scales through several pathways (Holloway et al, 2000;Li et al, 2002;Liu et al, 2003;Duncan and Bey, 2004;Huntrieser and Schlager, 2004;Liang et al, 2004;Weiss-Penzias et al, 2004;Auvray and Bey, 2005;Drori et al, 2012). The transatlantic long-range transport (LRT) is particularly *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%